Low-Thrust Transfer Design of Low-Observable Geostationary Earth Orbit Satellite - Bing Hua; Zhujun Shao (International Journal of Aerospace Engineering)
With radar and surface-to-air missiles posing an increasing threat to on-orbit spacecraft, low-observable satellites play an important role in low-thrust transfers. This paper presents the design for a low-thrust geostationary earth orbit (GEO) transfer control strategy which takes into consideration the low-observable constraint and discusses Earth shadow and perturbation. A control parameter optimization addresses the orbit transfer problem, and five thrust modes are used. Simulation results show that the method outlined in this paper is simple and feasible and results in reduced transfer time with a small amount of calculation. The method therefore offers a useful reference for low-thrust GEO transfer design.